2021
DOI: 10.1371/journal.pone.0247670
|View full text |Cite
|
Sign up to set email alerts
|

Impact of optical coherence tomography scan direction on the reliability of peripapillary retinal nerve fiber layer measurements

Abstract: Purpose To evaluate the intradevice repeatability and agreement for peripapillary retinal nerve fiber layer (pRNFL) measurements in healthy eyes with two different scan directions and two different number of B scans. Methods pRNFL was measured with a spectral domain optical coherence tomography on 54 healthy participants. Three-dimensional optic disc scans (6 mm x 6 mm) were performed on the right eye of the participants. Two repeated scans were performed in four different settings: H1: Horizontal scan with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…By contrast, the Wide scan and Cube scan in the current study are closer in scan density. It has also been reported previously that the scan direction affects precision, where horizontal scans have better repeatability than vertical scans 21 . The Wide scan in the prior study employed vertical B-scans, while the Optic Disc and Macular Cube scans were captured horizontally and vertically, respectively 15 , thereby potentially contributing to the varied repeatability between the Wide and Cube scans.…”
Section: Discussionmentioning
confidence: 58%
“…By contrast, the Wide scan and Cube scan in the current study are closer in scan density. It has also been reported previously that the scan direction affects precision, where horizontal scans have better repeatability than vertical scans 21 . The Wide scan in the prior study employed vertical B-scans, while the Optic Disc and Macular Cube scans were captured horizontally and vertically, respectively 15 , thereby potentially contributing to the varied repeatability between the Wide and Cube scans.…”
Section: Discussionmentioning
confidence: 58%
“…In all other sectors, the repeatability of the individual scan was better than combined scan. It has been reported previously that the scan direction affects the precision of the pRNFL measurements ( 12 ), where the horizontal sectors had better repeatability with horizontal scanning, whereas with the vertical scanning the repeatability was more homogeneous. In the present study, the combined scan, which had vertical B-scans, did not have a homogeneous repeatability among the sectors.…”
Section: Discussionmentioning
confidence: 91%
“…Clinical available OCTs have different scanning protocols for the macular and optic disc volumetric measurements. The built-in automated segmentation algorithm provides reliable volumetric measures of different retinal layers (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported previously that the scan direction affects precision, where horizontal scans have better repeatability than vertical scans. 21 The Wide scan in the prior study employed vertical B-scans, while the Optic Disc and Macular Cube scans were captured horizontally and vertically, respectively, 15 thereby potentially contributing to the varied repeatability between the Wide and Cube scans. With SS-OCT (DRI-OCT-1 Atlantis, Topcon), another study 8 , found comparably good repeatability of macular GCIPL and macular GCC thickness values from the Wide scan and Cube scans in healthy and glaucoma eyes; the current results are consistent with these earlier ones.…”
Section: Discussionmentioning
confidence: 99%